Evaluation of the stock enhancement effect of Phascolosoma esculenta on macrobenthic communities using diversity and biotic indices in Yueqing Bay, East China Sea - Yang, Yushu; Song, Chen; Chen, Peng; Lu, Wuyang; Han, Qingxi (Frontiers in Marine Science, 2024)
Stock enhancement activities have many benefits but also negative impacts. The macrobenthic diversity index and the M-AMBI index were adopted to assess the effects of stock enhancement of Phascolosoma esculenta on macrobenthic communities and the local ecosystem in Yueqing Bay. The results revealed that the Shannon-Wiener diversity index (H') and Margalef richness index (d) increased in October 2022 after stock enhancement, indicating a positive ecological restoration effect. The average M-AMBI in the intertidal zone of Yueqing Bay was 0.59, indicating good benthic ecological quality. Excluding seasonal factors, the M-AMBI in the intertidal zone increased after stock enhancement, indicating that stock enhancement by Phascolosoma esculenta had a certain positive effect on the intertidal ecological environment of Yueqing Bay. The increase in the M-AMBI occurred mainly in the low-tide zone, increased slightly in the mid-tide zone, and remained basically unchanged in the hightide zone. On the one hand, Phascolosoma esculenta can accumulate heavy metals from the environment and release a large amount of organic matter throughout its lifecycle, promoting nutrient cycling, which plays a positive role in the environment. On the other hand, Phascolosoma esculenta is an economic species; however, the planting of mangroves in the low tide zone causes fishers to fish in the mid-and high-tide zones, so the changes in the M-AMBI values in each tidal zone are related mainly to Phascolosoma esculenta and anthropogenic disturbances.